PEMBERDAYAAN KELOMPOK WANITA TANI OLEH DINAS PANGAN KABUPATEN KARAWANG - Cahyati Dewi; Kariena Febriantin; Rachmat Ramdani (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2022)
As an effort to empower women while optimizing the potential of the region, the government of Karawang Regency conducts a Women Farmer Group (KWT) training program. The women's farmer group in Karawang Regency focuses on the production of processed agricultural products which during their activities are fostered by the Food Service of Karawang Regency. In carrying out the KWT training program, the Food Service of Karawang Regency can be said to be successful in seeing the achievements that have been achieved, including the Mekarbuana village KWT which won the MSME exhibition in West Java and successfully marketed its products in the Karawang Tourist Village. The empowerment is carried out based on transformative, participatory and sustainable concepts through regional mapping, socialization, technical guidance and assistance.